2003
DOI: 10.1007/s00436-003-0875-9
|View full text |Cite
|
Sign up to set email alerts
|

Immunochemical characterization of alkaline phosphatase from the fluid of sterile and fertile Echinococcus granulosus cysts

Abstract: Alkaline phosphatase (ALP) from hydatid cyst fluid (HCF) was purified and characterized for comparison between fertile and sterile HCF. Samples were obtained from slaughtered sheep and then sterile and fertile cysts were separated. ALP was purified from aspirated cyst fluid and biochemical parameters were determined. Sera from patients with hydatid disease (15 samples) and patients with other parasitic diseases including fascioliasis (2 samples), taeniasis ( Taenia saginata, 5 samples) and also sera from uninf… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
7
0

Year Published

2004
2004
2018
2018

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 17 publications
0
7
0
Order By: Relevance
“…Two types of hydatid cysts can be observed in intermediate hosts: fertile cysts, on which protoscoleces are both joined to the germinal layer and free in the hydatid fluid filling the cyst cavity, and infertile cysts, which do not produce protoscoleces and are therefore unable to continue with the life cycle of the parasite [Kamenetzky et al, 2000; Lahmar et al, 2004]. The biological and molecular background underlying the generation of both types of cysts have not yet been elucidated [Vatankhah et al, 2003].…”
mentioning
confidence: 99%
“…Two types of hydatid cysts can be observed in intermediate hosts: fertile cysts, on which protoscoleces are both joined to the germinal layer and free in the hydatid fluid filling the cyst cavity, and infertile cysts, which do not produce protoscoleces and are therefore unable to continue with the life cycle of the parasite [Kamenetzky et al, 2000; Lahmar et al, 2004]. The biological and molecular background underlying the generation of both types of cysts have not yet been elucidated [Vatankhah et al, 2003].…”
mentioning
confidence: 99%
“…Zhang et al, 2017). In our previous study, we also showed significant differences between fertile and sterile cysts according to the kinetics and immunochemical characteristics of E.ALP (Vatankhah, Assmar, Vatankhah, & Shokrgozar, 2003).…”
mentioning
confidence: 71%
“…The enzyme was also proposed to be a marker for analyzing the effect of chemotherapeutical and interventional treatments of hydatid infection (Adnani Sadati, Farahnak, Molaei Rad, Golestani, & Eshraghiyan, ; Feng et al, ; R. Zhang et al, ). In our previous study, we also showed significant differences between fertile and sterile cysts according to the kinetics and immunochemical characteristics of E.ALP (Vatankhah, Assmar, Vatankhah, & Shokrgozar, ). Besides, detectable levels of antibodies against this enzyme in the sera of human patients confirmed that E.ALP can activate specific immune reactions in the host (Mahmoud & Abou Gamra, ).…”
Section: Introductionmentioning
confidence: 81%
See 2 more Smart Citations